2009
DOI: 10.1287/opre.1080.0645
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Optimization for a Make-to-Order Queue in an Uncertain Market Environment

Abstract: We consider a revenue-maximizing make-to-order manufacturer that serves a market of price-and delaysensitive customers and operates in an environment in which the market size varies stochastically over time. A key feature of our analysis is that no model is assumed for the evolution of the market size. We analyze two main settings: (i) the size of the market is observable at any point in time; and (ii) the size of the market is not observable and hence cannot be used for decision making. We focus on high-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 24 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…In other words, what can be done when a perfectly specified forecast model is unavailable to the seller? The present work also complements a recent paper by Besbes and Maglaras [2009] which studies issues similar to the ones here albeit in the context of admission control to a queue via modulating prices. Both of the above papers study the relevant systems in a limiting regime that produces a stochastic fluid model.…”
Section: Literature Reviewsupporting
confidence: 55%
“…In other words, what can be done when a perfectly specified forecast model is unavailable to the seller? The present work also complements a recent paper by Besbes and Maglaras [2009] which studies issues similar to the ones here albeit in the context of admission control to a queue via modulating prices. Both of the above papers study the relevant systems in a limiting regime that produces a stochastic fluid model.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Finally, our approach complements the perspective in Besbes and Maglaras (2009) and Haviv and Randhawa (2014), where the service firm does not fully know the demand (volume) information.…”
Section: Related Literaturementioning
confidence: 99%
“…For fixed i, H i (x) is decreasing in x and does not intersect with H j (x) for j = i. For any point (x, y) above the curve H i (x) and below the curve H i−1 (x) if i > 1, the optimal price for type-2 product is p i , while for any point (x, y) on or below the curve H K−1 (x), the optimal price for type-2 product is p K , and for any point (x, y) above the curve H 1 (x), the optimal price for type-2 product is p 1 .…”
Section: Structure Of the Optimal Policymentioning
confidence: 99%
“…He developed a deterministic fluid model to analyze the problem and construct near-optimal sequencing and pricing policies. Subsequently Besbes and Maglaras [1] developed a stochastic fluid model to analyze and make pricing recommendations for an MTO manufacturer operating in an environment with stochastically varying market size. Most recently, Cil et al [4] showed for the problem setting considered in Maglaras [9] that the optimal sequencing policy is a strict priority policy and established a number of monotonicity results for the optimal prices in terms of queue lengths.…”
Section: Introductionmentioning
confidence: 99%